COMMON-EDGE SIGNED GRAPH OF A SIGNED GRAPH - P. Siva Kota Reddy; E. Sampathkumar; M. S. Subramanya (IndoMS, 2010)
A Smarandachely k-signed graph (Smarandachely k-marked graph) is anordered pair....DOI : http://dx.doi.org/10.22342/jims.16.2.34.105-113